Effect of the fibre type on concrete impact resistance - Vivas, Juan Carlos (2020)
Fibre Reinforced Concrete performance is evaluated in terms of bending residual stresses. Although fibre concrete is suitable for structures exposed to impacts and other extreme loads, there is not much information about the relationship between the static residual capacity and the impact strength. Concretes incorporating steel, glass and polymer macrofibres were evaluated by means of a repeated dropweight impact test. The cracking resistance and the post-cracking behaviour were compared. While the first crack mainly depends on the matrix strength, there is a direct relationship between static residual stresses and the impact resistance, but it varies with the type of fibre.